Reaksi Radang pada Lidah dengan Tongue Piercing (Kajian in vivo pada Lidah Tikus Jantan Sprague dawley) - Feby Aryani; Afrini Puspita; Hendri Susanto (Faculty of Dentistry, Universitas Indonesia, 2015)
Today tongue piercing has become increasingly popular in the society. Several case reports associated with tongue piercing have presented various complications, such as tooth fracture, viral infection (HIV, Hepatitis B and C, herpes simplex, Epstein Barr), fungal infection (Candida spp), pain altered taste, edema, paresthesis, gingival recession, prolonged bleeding, contact dermatitis. However, there is no scientific evidence to reveal hispathological change in tongue piercing. The aim of this study is to investigate the inflammation response to tongue piercing in Spraque Dawley rats. Eighteen Sprague Dawley rats were divided into one control group of 3 untreated rats and three experimental groups of 5 rats each, according to the duration of tongue piercing until the end of 1st week (A), 6th week (B) and 12th week (C). At the end of treatments, the rats were anesthetized and sacrifices. Paraffin embedded tongue specimens were prepared for histological examination with H&E stainig. The number of inflammatory cells (PMN leukocytes, lymphocytes, macrophages) was counted under light microscope. All experimental procedures were carried out under approval of study protocol by the Health and Medical Research Ethics Committee, Faculty of Medicine, Gadjah Mada University, Yogyakarta. The results of this study indicated that the number of PMN leukocytes, lymphocytes, and macrophages was increasing to the 1st week after tongue piercing. The number of lymphocytes and macrohpages was still increasing after 6th and 12th weeks of piercing, but the bumber of PMN leukocytes, lymphocytes, and macrophages between the groups of 1st, 6th, and 12th weeks after piercing. It was concluded that tongue piercing induce inflammatory response for 12 weeks in Sprague Dawley rats.